2021
DOI: 10.1136/bmjophth-2020-000663
|View full text |Cite
|
Sign up to set email alerts
|

Role of interferon gamma release assay in the diagnosis and management ofMycobacterium tuberculosis-associated uveitis: a review

Abstract: Tuberculosis (TB)-associated uveitis is a common cause of infectious uveitis in the developing world. Diagnosis of TB uveitis remains a challenge. The role of interferon gamma release assays (IGRAs) is uncertain. Herein we summarise the available literature on the utility of IGRAs in the diagnosis and management of TB uveitis. We searched PubMed database from 1 August 2010 to 31 July 2020 using the following keywords alone and in combination: ‘interferon-gamma release assay’, ‘QuantiFERON’, ‘T-SPOT.TB’, ‘TB uv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…To our knowledge, several studies have been conducted on the usefulness of monitoring the response to ATT in active or latent TB; however, the exact role of IGRAs in monitoring treatment response in TBU remains undefined. Additionally, no study has reported the accuracy and clinical application of QFT-Plus in TBU [47] . The evidence of using new generations of IGRAs in TBU is still lacking.…”
Section: Role Of Interferon-gamma Release Assays In Tuberculousmentioning
confidence: 99%
“…To our knowledge, several studies have been conducted on the usefulness of monitoring the response to ATT in active or latent TB; however, the exact role of IGRAs in monitoring treatment response in TBU remains undefined. Additionally, no study has reported the accuracy and clinical application of QFT-Plus in TBU [47] . The evidence of using new generations of IGRAs in TBU is still lacking.…”
Section: Role Of Interferon-gamma Release Assays In Tuberculousmentioning
confidence: 99%
“… 7 The IGRA test was introduced in 2001 for the assessment of the IFN‐γ released by T‐cells following stimulation by antigen‐specific to Mycobacterium tuberculosis . 8 Following the COVID‐19 pandemic, the IGRA assays for SARS‐CoV‐2 were also developed. Currently, two types of IGRA tests are available for evaluation of the IFN‐γ released by T‐cells following the COVID‐19 vaccination or SARS‐CoV‐2 infection: Quanti‐FERON (QFN) SARS‐CoV‐2 (QIAGEN) and T SPOT Discovery SARS‐CoV‐2 kit (Oxford Immunotec).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of hosts can be infected by mycobacteria, complicating efforts at disease control [ 2 ]. TB, which is still considered a major health threat of public health concern, causes an estimated 8.6 million new cases and 1.3 million deaths annually [ 3 ]. Hence, the rapid and accurate diagnosis of TB is critical.…”
Section: Introductionmentioning
confidence: 99%